FUNDAMENTALS OF THE IMPLEMENTATION OF PEDAGOGICAL INNOVATIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses such issues as the introduction of innovative technologies in the educational process, the use of innovative technologies in reforming the education system, innovative education, the classification of innovations in an innovative educational environment.